Analysis of Operational Material Management Strategies to Avoid Overstock and Stockout in Packaging Inventory at Electronic Manufacturer Company - Siregar, Sonya; Wirawan, Adhitomo; Arif, Muhammad; Fajrin, Aulia (Journal of Collaborative Industrial Management (JCIM), 2025)
The manufacturing industry faces challenges in inventory, including overstock and  material stockouts that require companies to use an efficient inventory strategy. The purpose of this research is to analyze the effectiveness of the operational material management strategy  in overcoming the problem  of overstock and stockout material packaging in the inventory process at electronic manufacturer company. This study uses a qualitative approach method by collecting data through interviews, observations, and documentation. Data analysis was carried out using fishbone diagrams to decipher the causative factors and pareto diagrams to identify the main factors. The results of the fishbone analysis  show that data input errors, multiple division of labor, material damage during production, asynchronous communication between the teams involved, lack of supervision, and poor employee rotation are the main causes. In addition, the results of Pareto analysis with (Pareto's law 20-80) the main factors that dominate 80% are in human factors 31%, material 27%, and machine 22%. Based on the results of the research, simple applications can be done by improving communication coordination, increasing the number of employees, conducting regular training, and optimizing the use of technology.